2014
DOI: 10.1097/pai.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Distinction of Renal Cell Carcinoma from Other Carcinomas With Clear-Cell Histomorphology

Abstract: Clear-cell renal cell carcinoma (CC-RCC) is the most common primary kidney malignancy, yet this morphology is not unique to renal primary tumors, as clear-cell variants of numerous nonrenal carcinomas of varying lineages exist. Therefore, because of CC-RCC's ability to metastasize to nearly any anatomic location, ancillary studies such as immunohistochemistry are often needed to establish the diagnosis. Despite CD10 and renal cell carcinoma monoclonal antibody (RCCma) being touted as sensitive and specific mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 32 publications
2
38
0
1
Order By: Relevance
“…Adipophilin is one of the important players in lipid metabolism, responsible for storage of lipid droplets in all types of cells [4, 5]. Some recent studies show that many tumors overexpress adipophilin [6–22], especially those with clear cell histology [10, 11]. Several small reports showed that renal cell carcinoma (RCC) cells also overexpress adipophilin [10, 11, 2327] and one major study [24] reported the prognostic role of this biomarker in clear cell subtype on transcript level.…”
Section: Introductionmentioning
confidence: 99%
“…Adipophilin is one of the important players in lipid metabolism, responsible for storage of lipid droplets in all types of cells [4, 5]. Some recent studies show that many tumors overexpress adipophilin [6–22], especially those with clear cell histology [10, 11]. Several small reports showed that renal cell carcinoma (RCC) cells also overexpress adipophilin [10, 11, 2327] and one major study [24] reported the prognostic role of this biomarker in clear cell subtype on transcript level.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, they are both also positive regarding clear cell from the ovary [10]. This patient was amongst others negative for estrogen, Ca-125, CD10 and PAX8.…”
Section: Discussionmentioning
confidence: 99%
“…PAX-2 was positive to ccRCC by 81% and was positive in 24% of clear cell morphology group. PAX-8 in ccRCCgroup was 100% positive and was 39% positive in the clear cell morphology group [11]. The study concluded that PAX-2 and PAX-8 are sensitive markers to ccRCC and they lose their specificity in the presence of mullerian tumor cells [11].…”
Section: Introductionmentioning
confidence: 97%
“…However, currently there is no consensus in regard to what biomarker should be used in RCC classification [10]. Various RCC associated biomarkers have been studied including PAX-2/PAX8, CAIX, adipophillin (ADP), CD10, and monoclonal antibody RCC marker (RCCma) [11]. PAX, CAIX and vimentin are biomarkers that might be promising in RCC prognostic significance nowadays.…”
Section: Introductionmentioning
confidence: 99%